A high performance fully bio-based epoxy thermoset from a syringaldehyde-derived epoxy monomer cured by furan-derived amine. Issue 1 (17th December 2020) - Nabipour, Hafezeh; Wang, Xin; Song, Lei; Hu, Yuan
Abstract : Owing to the outstanding mechanical strength and modulus, high T g, anti-flammability and anti-bacterial property, this fully bio-based epoxy thermoset is a promising substitute for DGEBA-based thermoset in high performance fire safe applications. Abstract : With the growing awareness of global warming and depletion of petroleum resources, the development of bio-based epoxy thermosets as an alternative to petroleum-based diglycidyl ether of bisphenol A (DGEBA) epoxy thermosets has generated extensive interest over the past decade. However, most of the bio-based epoxy thermosets studied to date are bio-based epoxy monomers or bio-based curing agents. In order to increase the biomass content in the resultant epoxy thermoset as high as possible, it is desirable to fabricate fully bio-based epoxy thermosets. In this study, we synthesized a bio-based epoxy monomer (SA-GA-EP) from syringaldehyde, as well as a bio-based curing agent (DIFFA) from furfurylamine. The fully bio-based epoxy thermoset was obtained through curing SA-GA-EP by DIFFA, while the commercial DGEBA epoxy thermoset was cured by 4, 4′-diaminodiphenylmethane (DDM) as a contrast sample. The glass transition temperature ( T g ) of the cured SA-GA-EP/DIFFA thermoset was as high as 204 °C, which was much higher than that of the DGEBA/DDM thermoset (143 °C). The tensile strength and elongation at break of SA-GA-EP/DIFFA were 57.4 MPa and 2.9%, respectively, which were comparable to those of DGEBA/DDM. Additionally, the cured SA-GA-EP/DIFFA thermoset displayed excellent intrinsic flame retardancy with UL-94 V-0 classification and a relatively high limiting oxygen index of 40.0%. The results of the cone calorimetry test also manifested that the peak heat release rate, the total heat release and the smoke production rate of SA-GA-EP/DIFFA significantly declined by 85%, 86% and 38%, respectively, compared to those of DGEBA/DDM. Moreover, bio-based epoxy exhibited antibacterial activities against Gram-positive S. aureus . Owing to these outstanding performances (including mechanical strength and modulus, high T g, intrinsic flame resistance and antibacterial properties), this fully bio-based epoxy thermoset is a green and promising substitute for DGEBA-based thermoset in high performance fire safe applications.